ANALYSIS OF TAX AMNESTY POLICY ON STATE REVENUE IN THE TAX SECTOR - Devi Puti Thesia; Eshaulin Br Sembiring; Yosua Gabe Maruli Sijabat; Carlo Munthe; Dewi Pika Lumban Batu (RADJA PUBLIKA, 2025)
Tax amnesty is a policy established by the government in taxation that provides tax forgiveness for taxpayers to comply with tax payments. This forgiveness is the elimination of taxes that were originally owed and are not subject to administrative or criminal penalties in taxation, but requires the disclosure of assets and the payment of redemption money as stipulated in Law No. 11 Article 1 of 2016. The purpose of the tax amnesty policy is to accelerate economic growth through asset transfers, which have the potential to increase domestic revenue, lower interest rates, improve exchange rates, and boost investment. The purpose of this study is to examine how tax amnesty works in achieving successful state revenue in the tax sector. The method used in this study is literature review, utilizing theoretical analysis and several scientific references. The results of the study indicate that tax amnesty has yielded positive results in terms of asset declarations by taxpayers exceeding targets, but it has been less optimal in terms of fund repatriation and redemption payments. As such, this policy faces challenges in terms of potential unfairness toward compliant taxpayers and misuse by non-transparent taxpayers.